2001
DOI: 10.1177/089484530102700404
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship of Psychological Separation and Parental Attachment to the Career Maturity of College Freshmen from Intact Families

Abstract: This study was designed to investigate how psychological separation and parental attachment are related to career maturity separately and simultaneously and to investigate the influence of gender on the relationships among these variables. Subjects were 82 single white college freshmen from intact families. Data analysis using a canonical correlation analysis revealed that although psychological separation is relevant, parental attachment plays a more important role in career maturity. The relationship among t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
34
0
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 31 publications
3
34
0
3
Order By: Relevance
“…The past 15 years have seen increased research on parental attachment as a relational variable linked to the development of career maturity in adolescents (Kenny, 1990; H. Y. Lee & Hughey, 2001).…”
mentioning
confidence: 95%
“…The past 15 years have seen increased research on parental attachment as a relational variable linked to the development of career maturity in adolescents (Kenny, 1990; H. Y. Lee & Hughey, 2001).…”
mentioning
confidence: 95%
“…Some researchers have reported that gender had little impact on the total score of career maturity (Barnes 2001;Lee and Hughey 2001). Others, however, have indicated that gender is a contributing predictor to career maturity (Kerka 1998;Kornspan and Etzel 2001;Trusty et al 1997), noting that parental involvement is a greater predictor of female adolescents' career development than of the career development of male adolescents (Gianakos 2001;Trusty et al 1997).…”
Section: Discussionmentioning
confidence: 93%
“…For the same reason, parents should promote cooperative and harmonious relationships among family members (Jodl et al 2001;Lee and Hughey 2001). One way of enhancing career development could be facilitating career-relevant communications between parents and adolescents (Young et al 2001).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Many scholars have identified family of origin as an important contextual factor in understanding career exploration during adolescence, finding that strong family relationships are related to greater career exploratory behavior (Blustein, ; Bryant, Zvonkovic, & Reynolds, ; Hartung, Porfeli, & Vondracek, ). For example, parental attachment (Blustein, Walbridge, Friedlander, & Palladino, ; Lee & Hughey, ) and the number of parent–child activities a family engages in (Bryant et al, ) have been shown to positively relate to career exploration during childhood. Knowing how important parental and familial influences can be on the career exploration behavior of adolescents seems to imply that foster youth (who might lack parental or familial attachment) may engage less often in career exploration.…”
Section: Literature Reviewmentioning
confidence: 99%